Comparación de modelos de cultura organizacional de las empresas Roca Colombia del sector privado y la Agencia Nacional de Minería del sector público (2019)
Organizational culture is a key element in the development of organizations, in Colombia many organizations in order to meet their objectives seek to improve and strengthen it, that is why a study has been made on models of Organizational Cultures in two real companies Colombia belonging to the Mining sector, the National Mining Agency and Roca Colombia. Although different in its scope and context because each of them belongs to different sectors (Public Sector and Private Sector) but equal in its economic scope which is mining, we sought to determine which elements share or differ in the application and development of the organizational culture in each of them and how they manage day by day through their missionary activities the strengthening of the same for the fulfillment of their objectives as an organization.